Transcranial Direct Current Stimulation as an Add-on Treatment to Cognitive-Behavior Therapy in First Episode Drug-Naïve Major Depression Patients: The ESAP Study Protocol - Carvalho, Sandra; Gonçalves, Óscar F.; Brunoni, André R.; Fernandes-Gonçalves, Ana; Fregni, Felipe; Leite, Jorge (Frontiers in Psychiatry, 2020)
Background: Major Depression Disorder (MDD) affects more than 264 million people worldwide (WHO). Current treatments include the use of psychotherapy and/or drugs, however, approximately 30 % of people do not respond to these treatments; or do not tolerate the side effects associated to the use of pharmacological interventions. Thus, it is important to study non-pharmacological interventions targeting mechanisms not directly involved with the regulation of neurotransmitters. Several studies demonstrated that tDCS can be effective for MDD. However, tDCS seems to have a better effect when used as an add-on treatment to other interventions, such as Cognitive Behavioral Therapy (CBT). Methods/Design: This is a parallel, randomized, double-blinded, sham-controlled clinical trial in which a total of 72 drug-naïve, first-episode MDD subjects (36 per arm) will be randomized to one of two groups to receive a 6-weeks of CBT combined with either active or sham tDCS. The primary outcome will depressive symptoms as assessed by the Montgomery-Asberg Depression Rating Scale (MADRS). The secondary aim is to test whether tDCS combined with CBT can engage the proposed mechanistic target, of restoring the prefrontal imbalance and connectivity, by changes over resting-state EEG. Discussion: This study evaluates the synergetic clinical effects of tDCS and CBT in the first episode, drug-naïve, people with MDD. First episode MDD patients provide an interesting opportunity, as their brains were not changed by the pharmacological treatments, by the time course, or by the recurrence of MDD episodes (and other comorbidities). Trial registration: This study is registered with the United States National Library of Medicine Clinical Trials Registry: NCT03548545 (https://clinicaltrials.gov/ct2/show/NCT03548545)